Pengaruh Kombinasi Pupuk Kandang Ayam dan Ekstrak Kompos Ampas Kopi terhadap Sifat Kimia Tanah Ultisol - Nor Dayah; Bambang Joko Priatmadi; Hairil Ifansyah (Acta Solum, 2023)
Ultisol has problems such as soil acidity <5.5, high Al saturation >42%, low organic matter <1.15%, low nutrients such as 0.14% N, P 5.80 ppm, and low base saturation < 35%. Chicken manure is an organic material that alters soil pH and increases total N, total P, and P uptake. Coffee grounds can increase pH, N nutrients, organic matter, available P, prevent fungal growth. The purpose of this study was to determine the effects of feeding chicken manure and coffee grounds compost extract in increasing pH, increasing N availability, decreasing exchangeable Al, and increasing P availability of Ultisol. The research method used was a one-factor Completely Randomized Design (CRD). Factors tested were chicken manure, coffee grounds compost extract, and a combination of the two up to five treatments. K0 = Control, no chicken manure and coffee grounds compost extract; K1 = Coffee grounds compost extract 4 kL ha-1; K2 = Chicken manure 2 tons ha-1; K3 = Chicken manure 2 tons ha-1 + coffee grounds compost extract 4 kL ha-1; K4 = Chicken manure 4 tons ha-1 + coffee grounds compost extract 8 kL ha-1. Each treatment was replicated four times for 20 experiments. The results showed that the application of chicken manure and coffee grounds compost extract decreased soil pH, and soil exchangeable Al and increased soil ammonium, nitrate and available P levels.